Microangiopathy—A Potential Contributing Factor to Idiopathic Polyneuropathy: A Mini Review - Samuelsson, Kristin; Press, Rayomand (Frontiers in Neurology, 2018)
Chronic idiopathic axonal polyneuropathy (CIAP) is a slowly progressive predominantly sensory axonal polyneuropathy. The prevalence of CIAP increases with age. The pathogenic cause of CIAP is unknown, though there are several prevailing etiological hypotheses. In this mini-review we will focus on the hypothesis of disturbed microcirculation in the vasa nervorum of peripheral nerves as a pathogenic cause of CIAP. There is an association between CIAP and metabolic risk factors. Furthermore, the phenotype of CIAP resembles diabetic neuropathy both clinically and electrophysiologically. In sural nerve biopsies from patients with diabetes mellitus, structural abnormalities indicating microangiopathy in the endoneurial microvessels are well documented. Similarly, sural microvessel abnormalities have been shown in patients with atherosclerotic non-diabetic peripheral vascular disease. However, the reported histopathological alterations of microvasculature in sural nerves of CIAP patients are inconsistent. Two studies report microangiopathic changes in CIAP sural nerves comparable with those found in patients with diabetic neuropathy. Conversely, another recent study showed no significant differences in the microangiopathic parameters in the endoneurial microvessels in the sural nerve biopsies from CIAP patients compared to controls without polyneuropathy. However, this CIAP patient group was younger compared to the patient groups in the other two studies. A general limitation with the published morphological studies are that different methods have been used in the assessment of microangiopathy and there is also a risk of subjectivity in the results. Immunohistochemistry studies of sural nerves with verification of microangiopathy using specific biomarkers would be of great interest to develop.